Degradation of 2,4-Dichlorophenoxyacetic acid by Pseudomonas fluorescens strain HH - Oanh, Nguyen Thi; Duc, Ha Danh; Huy, Tran Dat; Hien, Nguyen Gia; Huynh Nhu, Nguyen Thi (Academia Journal of Biology, 2018)
Pseudomonas fluorescens HH isolated from soil utilized 2,4-Dichlorophenoxyacetic acid (2,4D) as a sole carbon and energy source. The strain completely utilized 1.0 mM of 2,4D within 30 hr. The immobilized Pseudomonas fluorescens HH degraded 2,4D with higher rates compared to the rates of free-suspension cells. The determination of degradation and cell growth kinetics in exponential growth phase of bacteria showed that both fitted with the Edwards model, in which the maximal utilization rates and inhibition coefficient were 0.079 ± 0.008 mM/h and 0.820 ± 0.03 mM, respectively. The addition of glycerol as a cryoprotectant into alginate increased the survival of bacteria in beads during freeze-drying process, which resulted in reducing the adverse effects of bead lyophilization.